O cumprimento da sentença na Corte Interamericana de Direitos Humanos: análise do cumprimento das reparações no caso González e outras (“campo algodoeiro”) vs. México - Souza, Brisa Libardi de (2018)
This work has the objective of analyzing compliance withthe judgment of González et al. (“Cotton field”) VS. Mexico, identifying qualitative and quantitative aspects of the measures taken and not complied with. The article seeks to understand the factors by which states refrain from complying with the judgments of the Inter-American Court of Human Rights and how this influenced the compliance withthe means determined by the court in the “cotton field” case, using as theoretical contribution authors that analyze the compliance stage , As well as surveys that have performed quantitative analysis of the repairs that are most commonly breached by states. The findings allow us to conclude that the most important repairs in the cotton field, such as theinvestigation and punishment of those responsible for the killings, have not yet been carried out, which results in non-guarantee of the rights of the victims.